PENERAPAN MODEL PEMBELAJARAN TEAM GAME TOURNAMENT TERHADAP PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH SISWA - Ana Ratnasari; Evan Farhan Wahyu Puadi; Abdul Rosyid (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2017)
Implementation learning model of Team GameTournament to improve problem solving ability students. This study aims to determinethe problem solving math students with a model of learning Team Game Tournament,to know increase in the problem solving students with a model of learning Team GameTournament, as well as students learn the response to the Team Game Tournamentlearning model. This study using instruments tests description of the ability to evaluateproblem solving math students and use inquiries response students to learn theresponse students of learning applied. The results of the pretest known that wellblended score of problem solving math classes control is 5,8 while the experiment was7. Meanwhile the results of the posttest know that well blended scores problem solvingmath classes control is 18,15 and well blended scores problem solving math classesexperimental is 20,7. The results of the calculations score N-Gain obtained wellblended class experiments 0,68 and class control is 0,56. The result of the test t scoreN-Gain obtained tcount = 1,71. This means that after the treatment an inc experimentsbetter then the control. As an increase in the problem solving math classes experimentwas in the category of high. In addition to the results of the inquiries responsestudents, know that the students show response was positive against a model oflearning Team Game Tournament.